Prediction of the tensile strength of unidirectional carbon fiber composites considering the interfacial shear strength. (15th May 2017) - Na, Wonjin; Lee, Geunsung; Sung, Minchang; Han, Heung Nam; Yu, Woong-Ryeol
Abstract: The tensile strength of unidirectional (UD) carbon fiber composites was predicted considering the interfacial shear strength (IFSS). First, the effect of the IFSS on the load transfer to the surrounding fibers when a fiber was broken was analyzed using finite element method and then the stress concentration factor (SCF) of each surrounding fiber was determined. The multiple fracture number was calculated using the SCF and a statistical approach that can calculate the probability of fiber breakage propagation due to the stress concentration when the broken fibers exist in neighbor. Finally, the tensile strength of UD carbon fiber composites was predicted using the multiple fracture number and was compared with experimental results, demonstrating the validity of the current method. An optimal IFSS that can ensure the maximum tensile strength of UD carbon fiber composites is discussed based on the calculation results.